(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2020)
In any discussion relatii-Ig to financing of health care, drugs are given an undeserved high profile. Of particular interest is the procurement, distribution and rational use of drugs. In this editorial, the focus is on "rational use of drugs (RUD)" a phrase which has assumed an ominous connotation. Indeed the much publicised WHO Action Programme on Essential Drugs derives its legitimacy from RUD concept.